Efektivitas Sistem Informasi Manajemen Nikah Berbasis Web dalam Sistem Pelayanan Kartu Nikah Digital - Airul Fahruzi; Abid Rohmanu; Ahmad Junaidi (Journal of Economics, Law, and Humanities, 2023)
This research is motivated by the Decree of the Minister of Religion of the Republic ofIndonesia Number 892 of 2019, concerning Web-Based Simkah in the Digital MarriageCard service system following the PMA Circular Letter of the Director General ofIslamic Community Guidance Number B-2361/Dt.III/PW.01/07/2021 concerningCards Digital Marriage. This research aims to describe the application of the Web-BasedMarriage Management Information System orSimkah Web in the Digital MarriageCard service system in KUA Pitu District, Ngawi Regency, and its effectiveness. Themethod used in this research is a descriptive method with a qualitative approach, namelyresearch that seeks to reveal and interpret a developing phenomenon. The researchresults show thatSimkah Web in KUA Pitu District, Ngawi Regency, has beenimplemented but is still hampered, especially regarding the readiness of KUA humanresources. In several cases, people found difficulties using this application, including thecomplexity of inputting marriage data in printing Digital Marriage Cards. Thus, it canbe concluded that the implementation ofSimkah Web has helped make it easier for theKUA to collect marriage data throughout Indonesia. However, it is still not fullyimplemented effectively by the community as a basis for printing Digital MarriageCards in the KUA of Pitu District